Plasma rich in growth factors stimulates proliferation, migration, and gene expression associated with bone formation in human dental follicle cells - Hitoe Okada; Kosuke Takahashi; Naomi Ogura; Risa Tomoki; Ko Ito; Toshirou Kondoh (Elsevier, 2016)
Background/purpose: Plasma rich in growth factors (PRGFs), which is prepared from autologous blood from patients, has been reported with regards to bone regeneration for dental implants. Human dental follicle cells (hDFCs) have the capacity to commit to multiple cell types such as the osteoblastic lineage. The aim of this study is to evaluate the effects of PRGFs for mineralization in hDFCs. Materials and methods: PRGFs was prepared from whole blood centrifuged at 460g for 8 minutes. hDFCs isolated from the dental follicle with collagenase/dispase were cultured with growth medium or osteogenic induction medium (OIM) containing PRGFs or fetal bovine serum. Concentrations of the growth factors were examined using an enzyme-linked immunosorbent assay kit. A cell migration assay was used for two-dimensional movement. Gene expressions were examined with real-time polymerase chain reaction using a DyNAmo SYBR Green quantitative polymerase chain reaction kit. Results: The platelet concentration in PRGF Fraction 2 was 2.14-fold higher than in whole blood. White blood cells were not detected in PRGFs. Transforming growth factor-β levels were higher than insulin-like growth factor-1, platelet-derived growth factor-AB and -BB, and vascular endothelial growth factors in PRGF Fraction 2. Proliferation and migration by hDFCs increased in OIM supplemented with PRGFs in a dose-dependent manner and were higher in hDFCs cultured in OIM plus 10% PRGFs compared with OIM plus 10% fetal bovine serum. PRGFs upregulated the gene expression of type I collagen, osteomodulin, alkaline phosphatase, bone morphogenic protein-4, and transforming growth factor-β in hDFCs. Conclusion: PRGFs may promote bone regeneration due to it including high levels of growth factors.